Pengaruh Faktor Sosiodemografi dan Sosioekonomi Terhadap Literasi Keuangan Mahasiswa Fakultas Ekonomi Universitas Hasyim Asy’ari Tebuireng Jombang - Tafrijiyah Firdaus; Lik Anah (JFAS : Journal of Finance and Accounting Studies, 2020)
This study aims to determine whether the influence of sociodemographic and socioeconomic factors on the financial literacy of students of the Faculty of Economics at Hasyim Asy'ari University Tebuireng Jombang. Sociodemographic factors are represented by gender, place of residence, study program, year of generation, GPA, and parent education, while socioeconomic factors are represented by parent income and individual income. The population used in this study were all students of the Faculty of Economics (Management, Accounting, and Islamic Economics) as many as 316 students with the number of samples used were 177 students with a collection technique proportionate stratified random sampling. The data analysis technique used is ordinal logistic regression. The results of this study found that the variables that have an influence on financial literacy are study programs, while gender, place of residence, year of force, GPA, education of parents (father and mother), parent income, and individual income did not affect student financial literacy. In addition, this study also found that the level of financial literacy of students of the Faculty of Economics of Hasyim Asy'ari University was in the medium category, amounting to 75.82%.